# Top of Form Question 1 Complete the square for the expression. Also, identify the resulting expression as a binomial squared. x2 − 6x + ____ x2 − 6x + (−9)

Top of Form Question 1 Complete the square for the expression. Also, identify the resulting expression as a binomial squared. x2 − 6x + ____ x2 − 6x + (−9) = (x − 3)2 x2 − 6x + (−36) = (x − 6)2 x2 − 6x + 36 = (x + 6)2 x2 − 6x + 9 = (x − 3)2 Question 2 Solve the equation. x2 − 6x + 10 = 12 Question 3 Solve the equation. x2 − 6x + 10 = 12 Question 4 Solve the equation. x2 + 6x = 12 Question 5 Which of the following represents the function f(x) = x2 − 14x − 1 in vertex form? Identify the vertex. f(x) = (x + 7)2 + 48; (−7, 48) f(x) = (x − 7)2 − 50; (7, −50) f(x) = (x − 7)2 − 48; (7, −48) f(x) = (x + 7)2 + 50; (−7, 50)